Expert Answers

An illustration of the letter 'A' in a speech bubbles

factor X^3+X^2-6X

first factor X

==> x(x^2+x-6)

Now factor the equation (x^2+x-6)

==> x(x+3)(x-2)

If you need to obtain the eqution's roots, then you need to find x values in which the equation equals 0

==> x(x+3)(x+2)=0

==> x = 0, -3, and -2

 

Approved by eNotes Editorial Team
Soaring plane image

We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

  • 30,000+ book summaries
  • 20% study tools discount
  • Ad-free content
  • PDF downloads
  • 300,000+ answers
  • 5-star customer support
Start your 48-Hour Free Trial